2019
DOI: 10.1016/j.ebiom.2019.08.070
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-finger protein p52-ZER6 accelerates colorectal cancer cell proliferation and tumour progression through promoting p53 ubiquitination

Abstract: Background: Aberrant expression of p53 and its downstream gene p21 is closely related to alterations in cell cycle and cell proliferation, and is common among cancer patients. However, the underlying molecular mechanism has not been fully unravelled. ZER6 is a zinc-finger protein with two isoforms possessing different amino termini (Ntermini) in their proteins, p52-ZER6 and p71-ZER6. The biological function of ZER6 isoforms, as well as their potential involvement in tumourigenesis and the regulation of p53 rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
(68 reference statements)
0
26
1
Order By: Relevance
“…Previous studies reported that ZNF398 directly activates transcription 44 and is regulated by Oestrogen Receptor Alpha 44,55 . Two isoforms of ZNF398 have been described 44,55,56 , called p71 and p52. The shorter isoform (p52), lacks a N-terminal domain and promotes proliferation of cancer cells by ubiquitination of p53 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that ZNF398 directly activates transcription 44 and is regulated by Oestrogen Receptor Alpha 44,55 . Two isoforms of ZNF398 have been described 44,55,56 , called p71 and p52. The shorter isoform (p52), lacks a N-terminal domain and promotes proliferation of cancer cells by ubiquitination of p53 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Two isoforms of ZNF398 have been described 44,55,56 , called p71 and p52. The shorter isoform (p52), lacks a N-terminal domain and promotes proliferation of cancer cells by ubiquitination of p53 56 . In hPSCs the longer isoform (p71) is predominant and has been used in all our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to bear this in mind when considering the role of ZNF746 in a certain biological context like in Parkinson’s disease [35]. Intriguingly, a very recent report illustrated isoform-dependent functions for ZNF398 on a posttranslational level: Only the isoform lacking amino-terminal sequences including DUF3669 and a major part of KRAB-A formed a complex with tumor suppressor TP53 and MDM2 and thus enhanced ubiquitinylation and subsequent degradation of TP53 [54].…”
Section: Discussionmentioning
confidence: 99%
“…ZER6, known as well as ZNF398, has two main isoforms: P52-ZER6 and P71-ZER6 [ 110 ]. The p52-ZER6 isoform has high expression in colorectal cancer ( Figure 4 ), which coincides with disease progression [ 111 ]. Huang and colleagues provided evidence that p52-ZER6 (but not p71-ZER6) enhances the interaction between p53 and MDM2, which in turn augments p53 ubiquitination and degradation.…”
Section: Krab-zfps Roles In Cancer Cellsmentioning
confidence: 99%
“…ZER6 knockdown resulted in the increased expression of the p53 target, namely p21 ( Figure 6 B), which negatively regulates the cell cycle ( Figure 5 ). This further hindered cell proliferation in human colon carcinoma cell line HCT116 [ 111 ]. High p52-ZER6 expression was also detected in ER-positive breast cancer cell lines.…”
Section: Krab-zfps Roles In Cancer Cellsmentioning
confidence: 99%